Software for adaptive grid construction - A.N., Semakin (Trudy Instituta sistemnogo programmirovaniâ, 2018)
In this paper, we present a software package for the construction of an adaptive finite-difference grid by expanding physical variables into a sparse wavelet series. Some technical details of the program implementation are given. In particular, we describe data structures used for the grid representation in computer memory and tools for organizing parallel calculations on the adaptive grid. Also the results of several numerical simulations involving the developed package are shown.